Rede humana de relações: relações de sociabilidade a partir do acervo fotográfico de José Simeão Leal - Barros, Kelly Cristiane Queiroz (2012)
This research aimed to study the imagery information contained in the set of photographs belonging to the private arquive of José Simeão Leal and, from them, rewrite the sociability networks in which the editor was inserted. We had reflect on the importance of imagery information in the construction of memories, realizing the photography as support of memories, as traces of many social networks maintained by individuals and as a indiciary sign according to semiotics of Peirce. Our work proposes to make the documentary representation of the material searched, as proposed by the Information Science, after all, occurred the documentary research and mapping of the configurations formed (concept used by Norbert Elias) and represented in thephotographs. We had as reference on memory, among others, Paul Ricoeur; on imagery information we use the considerations of Jacques Aumont; on sociability networks we had the structural notion of web of human relationships , as proposed by Norbert Elias; dialogued about photography, among other with Phillipe Dubois, the author who made the connection with the semiotics of Charles Sanders Peirce, a philosopher to whom we report.